Teori Manajemen Konflik dalam Pendidikan dan Organisasi: Sebuah Literatur Review atas Pendekatan Konseptual dan Praktis - Rifkiatul Musarofah; Yusmi Afrida; Lailatul Munawaroh; Laila Silvi Romadhoni; Mu’alimin Mu’alimin (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Conflict management has become an increasingly important concern in various areas of life, whether in education, organizations, or society at large, especially in the face of the fast-paced dynamics of the digital age. The complexity of interactions between individuals and groups poses unique challenges that require conflict management strategies that not only focus on problem solving, but also aim to create harmony, collaboration, and increased productivity. This study aims to systematically review the literature discussing conflict management issues during the period 2020 to 2024. The two main questions asked are: (1) what are the latest trends and approaches in conflict management research, and (2) what conflict management strategies are most widely used in various social and professional contexts. The results of the review show that recent research highlights three main areas of conflict management application, namely in the context of education, the organizational work environment, and family life. Several dominant strategies that emerge include the importance of effective communication, active participation from all parties involved, the implementation of an adaptive organizational culture, and an approach based on social harmony values. Overall, this study confirms that conflict management is multidimensional and continues to evolve toward more strategic and contextual application. Future research is expected to integrate cross-disciplinary findings to develop conflict management models that are more responsive to the challenges of the digital age.